ANALISIS DAN PEMETAAN KERUSAKAN PERKERASAN JALAN DENGAN METODE BINA MARGA PADA RUAS JALAN KABUPATEN MALANG (STUDI KASUS: JALAN RAYA TALANGAGUNG - JALAN RAYA JATIKERTO) - Dimas Ardhandi Faishal Maulana; Hendrata Wibisana (LPPM Universitas Abdurrab, 2024)
In the Malang Regency area, several arterial roads experience pavement damage, such as on Jalan Raya Talangagung - Jalan Raya Jatikerto which is one of the arterial roads that can lead to Blitar Regency. Based on this phenomenon, it is necessary to conduct a review or research to determine the condition of the road pavement, so that it can help in making policies or choosing the right maintenance system. The method used in determining the condition of road damage is the Bina Marga method which has the final result in the form of a priority order value and mapping of road damage conditions in the research area using Geographic Information System (GIS) tools. Based on the results of the analysis and calculation, the damage conditions of the pavement are obtained namely, crocodile skin cracks, transverse cracks, longitudinal cracks, patches, grain release, fatness, random cracks, holes, and grooves. Then the priority order value on Jalan Raya Talangagung is 5, so the road is included in the periodic maintenance program, while on Jalan Raya Jatikerto a priority order value of 3 is obtained, so the road is included in the improvement program. The next step when obtaining the condition value of each road is to apply the Geographic Information System as a tool in creating thematic maps that show the condition value of road damage for each road in the research location.